فهْم النص القرآني في الدراسات المعاصرة بيــن النقل والعقــــل - الحوات, الهاشمي برعدي (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This research is an attempt to explore the scientific methodology employed in understanding the Quranic text, as adopted by traditional scholars who uphold the integration of both revelation (naql) and reason (‘aql), in contrast to contemporary modernist reformers who prioritize reason and elevate it above any interpretive tradition. The study asserts that a sound understanding of the Quranic text must be grounded in a balance between transmitted knowledge and rational inquiry. The primary objective of this research is to clarify the methodological approach that should be followed in interpreting the Quran—one that harmonizes revelation with reason. It also aims to examine the rationalist approach of some contemporary scholars, who interpret the Quranic text through a historical and contextual lens, arguing that traditional interpretations are no longer suitable for the modern world due to the evolving circumstances of its audience. According to this perspective, understanding the Qur’an requires a new scientific methodology that connects the text to people’s lived realities and historical contexts. The ultimate aim of such reformers is to approach the Quranic text as a human construct—subject to evolving cultural frameworks and reinterpretation across generations, which constitutes the central problem of this study. The research adopts an analytical and critical methodology, ultimately concluding that genuine understanding of the Quranic text necessitates the integration of both revelation and reason. Sole reliance on reason, divorced from revelation, leads to a flawed and unstable interpretation.